DETERMINATION OF THE EFFECTIVENESS AND USE OF SOME ANTHELMINTIC DRUGS IN THE TREATMENT OF FASCIOLOSIS IN GOATS - I.A, Hazratqulov; I.G, Usmanov; B.Sh, Raximberganov (Journal of Medical Genetics and Clinical Biology, 2024)
In this article, the effectiveness of the newest anthelmintic drugs in the treatment of fasciolosis in goats in the irrigated areas of Surkhandarya region was determined